Comparative analysis of the flexibility of endodontic instruments, submitted or not to thermal treatment (Pesquisa Odontológica Brasileira, 2000)
The aim of this study was to evaluate the bending resistance of 2 types of files: K and Flexofile®, from different numbers submitted or not to a recrystallizing thermal treatment. A hundred and forty-four files were submitted to the bending test in a torquemeter with a scale. The results made evident that the recrystallizing thermal treatment was able to cause a decrease on the bending resistance of the K type files between 56.78 and 82.06% (alpha = 0.05%). The Flexofile® files presented a decrease on the bending resistance between 1.94 and 50.60% (alpha = 0.05%), in comparison with non-treated Flexofile® files, except for number 25. In conclusion, the recrystallizing thermal treatment, as proposed, reduces the bending resistance of K type files in a significant way, and of Flexofile® files in a less marked way.